Relationship between the functional reserve of the heart and the physical facility of adolescents of the special medical group - Sitovskyi, Andrii M.; Andriychuk, Olha Ya.; Usova, Oksana V.; Yakobson, Olena O.; Ulianytska, Nataliia Ya.; Tsjupak, Tetiana Ye. (My University, 2021)
Relevance. The most common indicators for assessing the effectiveness of health technologies are the cardiovascular performance of adolescents. At present, there is insufficient information on the quantitative substantiation of informativeness, prognostic and diagnostic significance of such indicators in the process of orrection of functional and reserve capabilities of the cardiovascular system of adolescents. Objective: to determine the levels of functional reserve of the heart according to the Rufier index and to study the physical performance of students aged 12-14 years of different medical groups. Materials and methods. 178 seventh-eighth-graders aged 12-14 (85 boys and 93 girls) were examined. All students voluntarily participated in this experiment, and the written consent of their parents was obtained. Physical performance was studied according to the parameters of the bicycle ergometric test PWC170. The division of students into medical groups was carried out according to the indicators of the level of functional and reserve capabilities of the cardiovascular system, conducted according to the Rufier index. Statistical analysis of the results was performed using the application package Statistica-V.10.0. The normality of the distribution was checked by the Kolmogorov-Smirnov test. The studied indicators are described by the median (Me) and 25, 75 percentiles. The relationships of the studied indicators were analyzed according to Spearman’s rank correlation coefficients. To determine the reliability of differences in indicators used the criterion of Kraskel Wallis. Results. The main group included 13.5% of adolescents, the preparatory group – 35.4%, the special medical group – 51.1% of students. Among student-athletes, 25.9% of boys and 45.4% of girls belong to a special medical group. In school athletes, the correlations between the Rufier index and the PWC170 test are low and statistically insignificant. Indicators of physical performance in the range of 25-75 percentiles do not differ in different medical groups. This indicates that in a special medical group there are students with medium and high levels of physical fitness. Conclusions. The established age and gender differences in the functional reserve of the heart of schoolchildren determine the need to develop differentiated approaches to the assessment of the Rufier index. Physical performance in different medical groups varies in a fairly wide range. The division of students into medical groups according to the Rufier index does not reflect the level of physical performance of students and, accordingly, their real adaptive capabilities. Further studies are needed on the informativeness of using the Rufier test to divide students into medical groups.
Взаємозв’язок функціонального резерву серця та фізичній працездатності підлітків спеціальної медичної групи
Keywords: adolescents; Rufier’s test; physical performance; medical groups; 612.176-053.5-073:796.011.1